Глоттодидактические аспекты кросскультурного образования и коммуникации - Pacholczyk, Tadeusz (Glottodidactica, 2007)
In the introductory remarks the author emphasises that intercultural education through the foreign language correlates not only with the basic assumptions of modernising the teaching/learning of foreign languages, put forward by the Council of Europe, but most of all with the humanistic aspects of the teaching content, which should aim at shaping the homo moralis and homo communicus. The following general eterminants are distinguished in the exploration of the problem: cognitive, psychological, didactic-sociocultural and pedagogical. Then the author characterises in detail the socalled base determinants, i.e. the intercultural and linguistic-cultural competencies, and discusses the factors determining the shaping of these competencies.